THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURSHIP INTENTION MEDIATED BY SELFEFFICIENCY IN JAKARTA STATE UNIVERSITY STUDENTS - Syaputri, Shyndy; Purwana, Dedi; Usman, Osly (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This purpose of this study is to explain the effect of entrepreneurship education to entrepreneurial intention mediated by self-efficacy of student on Universitas Negeri Jakarta 2018. The research method used is the survey method. The sample used in this study was obtained by 161 respondents from students of Universitas Negeri Jakarta. Data collection is done through the dissemination of questionnaires using the likert scale. Based on research conducted there is a self-efficacy mediates positively and significantly the indirect effect of entrepreneurship education on entrepreneurial intentions